HIV testing in the maternity ward and the start of breastfeeding: a survival analysis - Glaucia T. Possolli; Márcia L. de Carvalho; Maria Inês C. de Oliveira (Brazilian Society of Pediatrics, 2015)
Objective: The purpose of this study was to analyze the influence of the time between birth and the beginning of breastfeeding, especially at the moment of the rapid HIV test results at hospital admission for delivery. Methods: Cohort study of 932 pregnant women who underwent rapid HIV test admitted in the hospital for delivery in Baby‐Friendly Hospitals. The survival curves of time from birth to the first feeding were estimated by the Kaplan‐Meier method and the joint effect of independent variables by the Cox model with a hierarchical analysis. As the survival curves were not homogeneous among the five hospitals, hindering the principle of proportionality of risks, the data were divided into two groups according to the median time of onset of breastfeeding at birth in women undergoing rapid HIV testing. Results: Hospitals with median time to breastfeeding onset at birth of up to 60 minutes were considered as early breastfeeding onset and those with higher medians were considered as late breastfeeding onset at birth. Risk factors common to hospitals considered to be with early and late breastfeeding onset at birth were: cesarean section (RR = 1.75 [95% CI: 1.38 to 2.22]; RR = 3.83 [95% CI: 3.03 to 4.85]) and rapid test result after birth (RR = 1.45 [95% CI: 1.12 to 1.89]; RR = 1.65 (95% CI: 1.35 to 2.02]), respectively; and hospitals with late onset: starting prenatal care in the third trimester (RR = 1.86 [95% CI: 1.16 to 2.97]). Conclusions: The onset of breastfeeding is postponed, even in Baby‐Friendly Hospitals, when the results of the rapid HIV test requested in the maternity are not available at the time of delivery.